Efforts to Improve Student Learning Outcomes on the Material of Faith in the Prophet of Allah SWT Through the Course Review Horay Learning Model at SMK Negeri 1 Gandapura - Hafnidar; Risma (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
This study discusses improving student learning outcomes in the material of Faith in the Messenger of Allah SWT through the application of the Horay Course Review (CRH) Learning Model in grade XI of SMK Negeri 1 Gandapura semester I of the 2021/2022 academic year. The main purpose of this study is to find out the extent to which the CRH learning model can improve student learning outcomes in the material. This research uses a qualitative approach with the type of Class Action Research (PTK) which is carried out in two cycles. Data were collected through test and non-test techniques, where the test instrument was in the form of multiple choice, while non-test data was analyzed qualitatively descriptive, and test data was analyzed using descriptive percentages. The research subjects consisted of 27 students in grade XI. The results showed that at the end of cycle I, students who achieved a score of ≥70 were only 59.25%, while the activity of teachers and students averaged 71.85%. After improvements were made in cycle II, students who obtained a score of ≥70 increased to 81.48% with the average activity of teachers and students reaching 82.68%. Thus, the use of the Horay Course Review learning model has proven to be effective in improving student learning activities and outcomes on the material of Faith in the Messenger of Allah SWT at SMK Negeri 1 Gandapura.